Labor Income Polarization in Greater Buenos Aires - Mariana Viollaz; Sergio Olivieri; Javier Alejo (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2009)
This paper presents and analyzes a group of statistics which characterize the level and evolution of the labor income polarization in Greater Buenos Aires over the past two decades (1986-2006). The empirical evidence reveals two stages throughout those years: the first one distinguished by an increment of all indices and the second one, by shrinkage of them. Inspecting potential factors which could explain those changes, returns to education surge as the main polarization force in the labor market. Hence, an equalizing distribution of the human capital is a possible alternative for a less polarized labor market.
Keywords: I3; D3; D6; 330; polarization; labor; cohesion; inequality; Argentina; Greater Buenos Aires